Metaphors in Russian Poetry Translations into Tatar - Fakhrieva, Leilya Khambalevna; Kirillova, Zoya Nikolaevna; Alkaya, Ercan (Karabuk Univ, 2017)
A comparative study of Russian poetry Tatar translations is performed in this scientific article, in particular, the poems by A. Pushkin, M. Lermontov, N. Nekrasov with the original to analyze lexical expressive means, namely the metaphors of the original. The following methods and techniques were used in the work: comparative and hermeneutic. The study is based on the translation of poems by A. Pushkin, M. Lermontov and N. Nekrasov, which was performed by Tatar writers A. Iskhak, A. Yunus, M. Sadri, A. Faizi, A. Erikay and N. Arslanov. The choice of authors and their works is conditioned not only by their popularity, but also by the peculiarity of their literary language, the distinctive feature of which are original pictorial and expressive means. On the basis of poem analysis from the point of view of lexical pictorial means of the language use, it was revealed that the language of the selected writers has a rich imagery and a high degree of metaphorization. The authors analyze the issues of metaphor adequate embodiment concerning the poetry by A. Pushkin, M. Lermontov, N. Nekrasov in Tatar language. The problem of the original meaning recreation is considered with the preservation of its form features. This problem is faced by the translators of a poetic text.
Keywords: Pushkin's poetry; Lermontov's poetry; Nekrasov's poetry; Poetic text; Artistic translation; Lexical means of expressiveness; Metaphor